Ecology of Indian Roofed Turtle, Pangshura tectum (Gray 1831) in Bangladesh - Hossai, Md. Lokman; Sarker, Shomb Uddin; Sarker, Noor Jahan (Ecoprint: An International Journal of Ecology, 2009)
lndian roofed turtle, Pangshura tectum, was found in all types of aquatic habitats in Bangladesh. Of the 8 categories of habitats studied, the highest number (42.74%) was found in domestic ponds followed by derelict ponds, tanks, marshlands, canals, agriculture fields, lakes, streams and puddles. Most of the time the turtle was found in basking condition (60.09%), while rarely it was observed in burrowing condition. In addition to this, Indian roofed turtle spent 31.75% time in feeding and 8.16% in browsing. Key words: Indian roofed turtle, ecology, habitat preference, behavioural patterns doi: 10.3126/eco.v13i0.1621 Ecoprint (An International Journal of Ecology) Vol. 13, No. 1, 2006 , Page 1-8